Recent Formulation Advances and Therapeutic Usefulness of Orally Disintegrating Tablets (ODTs) - Maimoona Chinwala (MDPI AG, 2020)
This review highlights the recent formulation advances (different methods of preparation involving various novel approaches) that have been advancing the use of ODT as a popular dosage form. Furthermore, the important characteristics of ODTs that are required for patient compliance and appropriate therapeutic benefit are discussed. In addition to conventional ODTs, ODTs formulated for controlled release of pharmaceuticals and taste masking are also discussed.